Male Dominance Related Self-Deception Among Women - Hrgović, Josip (Array, 2006)
Numerous findings suggest that self-deception positively influences various mental states, including depression. Likewise, many studies have shown that there is a negative correlation between socio-economic status and depression. In most human cultures men are the socially dominant gender, and at the same time, the incidence of depression is higher among women. It could be hypothesized that self-deception has an adaptive function of reducing depression among women. To test this hypothesis, we explored the relationship between self-deception, depression, and attitudes towards male dominance, as a function of socio-economic status of the respondents, among 110 female students of the University of Zagreb. The results are interpreted in the context of adaptiveness of self-deception in women, regarding male dominance.